His and Her Earnings Following Parenthood in the United States, Germany, and the United Kingdom. Issue 4 (August 2020) - Musick, Kelly; Bea, Megan Doherty; Gonalons-Pons, Pilar
This article advances a couple-level framework to examine how parenthood shapes within-family gender inequality by education in three countries that vary in their normative and policy context: the United States, Germany, and the United Kingdom. We trace mothers' share of couple earnings and variation by her education in the 10-year window around first birth, using long-running harmonized panel surveys from the 1990s and 2000s ( N = 4, 117 couples and 28, 488 couple-years) and an event study methodology that leverages within-couple variation in earnings pre- and post-birth. Our results show steep declines in her share of couple earnings following first birth across the three countries that persist over several years of follow-up. Declines are smallest in the United States, due to U.S. mothers' higher employment and longer work hours. Declines are also smaller among female partners without a college degree in the United States, where mothers have less work-family support and fewer options to manage work and family on one income. Results shed light on how parenthood plays into gender inequality within couples, and how country context shapes couple dynamics and inequality across households.